Adding New Dimensions to Protein Structures with Room-Temperature Serial Crystallography - Hannah Glover (CHIMIA, 2025)
Structure-based drug design (SBDD) uses experimentally determined structures of proteins to aid in the identification of hits and development of leads for protein targets. Improving the physiological relevance of protein structures that are routinely determined at cryogenic temperature will undoubtedly help to improve this design process. One way that this can be achieved is through serial crystallography; a method that can be used to determine the high-resolution structure of proteins at room temperature. Additionally, through the application of time-resolved serial crystallography, protein dynamics can be investigated – providing another dimension to protein structure determination. How this information can be used to guide SBDD is yet to be seen. This article gives a brief overview into serial crystallography, including the experimental challenges faced by researchers in the field and some recently published pharmacologically relevant proteins studied using this technique.